ACUTE DISTURBANCE OF BLOOD CIRCULATION IN THE HEAD - Mo‘minjonov A.A.; Mamatojiyev Sh.A.; Nurmetov X.T. (Лучшие интеллектуальные исследования, 2024)
Abstract: Acute cerebrovascular accident, commonly known as stroke, is a medical emergency that occurs when blood flow to the brain is disrupted. This can lead to serious complications such as brain damage, disability and even death. Stroke has been a significant health problem throughout history, and researchers, doctors, and scientists have worked tirelessly to better understand and treat the condition. In the past, strokes were often misunderstood and misdiagnosed. Ancient civilizations such as the Egyptians and Greeks believed that strokes were caused by supernatural forces or evil spirits. It was only in the 17th century that the French doctor Jacob Winslow discovered the connection between strokes and the brain. Winslow’s groundbreaking work laid the foundation for future research in the field of acute cerebrovascular disorders. In the 19th century, the German neurologist Karl Wernicke made a significant contribution to the understanding of stroke. Wernicke identified a specific area in the brain responsible for language, now known as Wernicke’s area. He also discovered that damage to this area can lead to a condition called Wernicke’s aphasia, a language disorder common in stroke patients. Wernicke’s research helped pave the way for further research into the effects of stroke on cognitive function.